HIV and syphilis in migrant workers in eastern China. Issue 1 (3rd February 2006) - Hesketh, T; Li, L; Ye, X; Wang, H; Jiang, M; Tomkins, A
Abstract : Objective: To measure the prevalence of HIV and syphilis in migrant and urban workers in eastern China, and to determine their knowledge and attitudes towards HIV. Methods: A cross sectional survey involving dried blood spot testing and self completion questionnaires. Migrants and urban workers in 39 work units in two districts of Hangzhou, Zhejiang Province, were recruited. Respondents completed a questionnaire about knowledge and attitudes towards HIV. Testing for antibodies to HIV-1 and syphilis was carried out on dried blood spots using a gelatin particle agglutination technique. Results: Data were obtained from 4148 migrants and 2197 urban workers. There were no HIV infections detected in either the migrant or urban populations. Syphilis was detected, but the prevalence was not significantly different between urban workers (0.68%, 95% CI: 0.35 to 1.02) and migrant workers (0.48%, 95% CI 0.26 to 0.66, p = 0.07). 36% of the migrants had migrated with a partner, and 7% had also migrated with children. Urban workers were consistently more knowledgeable than migrants about HIV, but knowledge of the major modes of transmission was good in both groups. Traditional attitudes to sexual behaviour were still pervasive in both groups and attitudes towards individuals with HIV were generally intolerant. The use of sex workers appears rare and no more common in migrants than urban workers. Conclusion: At present HIV is probably not spreading in the internal migrant population in eastern China. Syphilis is a problem in both the migrant and urban populations. The tendency to migrate with partners makes migrants relatively low risk for engaging in casual sex.